2021
DOI: 10.3389/frph.2021.726936
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Cannabinoid Agonist WIN 55212-2 Targets Proliferation, Angiogenesis, and Apoptosis via MAPK/AKT Signaling in Human Endometriotic Cell Lines and a Murine Model of Endometriosis

Abstract: Endometriosis (EM) is characterized by the growth of endometrium-like tissue outside the uterus, leading to chronic inflammation and pelvic pain. Lesion proliferation, vascularization, and associated inflammation are the hallmark features of EM lesions. The legalization of recreational cannabinoids has garnered interest in the patient community and is contributing to a greater incidence of self medication; however, it remains unknown if cannabinoids possess marked disease-modifying properties. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Higher levels of these cytokines fuel hyperalgesia which is further sustained through altered expression of TRPV1 in the peritoneum of EMS patients (Rocha et al 2011). In a mouse model of EMS, we demonstrated significantly reduced expression of TRPV1 in lumbar DRGs upon exposure to WIN 55,212-2 as compared to sham mice (without EMSlike lesions), suggesting that nociceptive pain might be modulated by DRGs whose terminals are in proximity to EMS lesions (Lingegowda et al 2021b). Similarly, a study using a rat model of EMS also showed that the stimulation of the CB1 and CB2 receptors using WIN 55,212-2 significantly reduced abdominal nociception and vaginal hyperalgesia in a CB1 receptor-dependent manner (Dmitrieva et al 2010).…”
Section: The Endocannabinoid System and Painmentioning
confidence: 75%
See 1 more Smart Citation
“…Higher levels of these cytokines fuel hyperalgesia which is further sustained through altered expression of TRPV1 in the peritoneum of EMS patients (Rocha et al 2011). In a mouse model of EMS, we demonstrated significantly reduced expression of TRPV1 in lumbar DRGs upon exposure to WIN 55,212-2 as compared to sham mice (without EMSlike lesions), suggesting that nociceptive pain might be modulated by DRGs whose terminals are in proximity to EMS lesions (Lingegowda et al 2021b). Similarly, a study using a rat model of EMS also showed that the stimulation of the CB1 and CB2 receptors using WIN 55,212-2 significantly reduced abdominal nociception and vaginal hyperalgesia in a CB1 receptor-dependent manner (Dmitrieva et al 2010).…”
Section: The Endocannabinoid System and Painmentioning
confidence: 75%
“…This is particularly important in EMS, as lesion proliferation and chronic inflammation are key hallmarks of the disease, and the activity of MAPK family proteins is significantly higher in EMS (Cakmak et al 2018). We and others have shown that stimulation of cannabinoid receptors using a synthetic cannabinoid (WIN 55,212-2) in endometriotic cells (in vitro) directly attenuates the MAPK signaling cascade, further reducing inflammation and proliferation in these cells (Lingegowda et al 2021b;Leconte et al 2010). Anti-inflammatory and analgesic effects are the two most sought-after properties of ECS, as EMS patients generally suffer from both inflammatory pain and neuropathic pain.…”
Section: The Endocannabinoid System and The Inflammatory Response In ...mentioning
confidence: 96%
“…Our mouse model of endometriosis has been extensively used to gain mechanistic insights into the complex pathophysiology of endometriosis in previously reported studies 34,6163 . Indeed, we identify significantly increased numbers of large, multinucleated cells in lesions obtained from IL-23 treated mice as compared to controls (PBS).…”
Section: Discussionmentioning
confidence: 99%
“…EM was surgically induced as described previously 2,17 . Two independent groups (DD and UnD) per genotype were used in this study ( n = 8-16).…”
Section: Methodsmentioning
confidence: 99%
“…In EM, CNR1 and CNR2 activation aids in controlling lesion proliferation, pain, and vascularization 17,18 . Keeping in view dysregulated ECS signalling and their central role in decidualization and fertility, we hypothesize that altered CNR1 and CNR2 expression will disrupt ECS signaling dynamics, leading to further lesion development.…”
Section: Introductionmentioning
confidence: 99%